The Influence of Intellectual Property Rights (IPR) on ASEAN+5’s International Trade (IT) - Manickam, Hemleen Soosai; Idris, Sidah; Nipo, Debbra Toria (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
In accordance with the ASEAN IPR Action Plan 2016-2025, this study explores the connections and causality of Intellectual Property Rights (IPR) on international trade (IT) of ASEAN+5 countries represented by Malaysia, Thailand, the Philippines, Singapore, and Indonesia. According to this, international trade is measured in terms of trade (as a percentage of GDP). IPR is measured by patent applications filed by residents, patent applications filed by non-residents, industrial design applications filed by residents, and industrial design applications filed by non-residents. Along with IPR, the effect of government effectiveness (GE) on IT is also investigated. Foreign direct investment (FDI) and inflation are also utilized as control variables. This study adopts new growth theory as to further explain the variables involved. All ASEAN+5 data for the individual variables were derived from the World Bank Development database, and the panel dataset was investigated using the PFGLS estimator and Dumitrescu-Hurlin test for over 21-years period (2000-2020). The findings of this study revealed a strong effect between IPR and IT as well as a unidirectional relationship between IPR (except industrial design application, filed by residents) and IT for the ASEAN+5 region. The limitation of this study is that it only focused on five ASEAN countries, and the selection of IPR indicators was limited. Nevertheless, this study provides some important insights for policymakers and local merchants to focus and invest more on IPR in order to promote ASEAN’s international trade in accordance with global norms.